Arjasa Village farmer assistance in cassava peel and Trichoderma fungus processing as organic fertilizer - Andrew Setiawan Rusdianto; Aqlima Sekar Maulina; Damai Puspita Budiarso; Ratih Dewi Anggraini; Noviatul Mud'Rovin Nahar; Lestari Lestari; Iqlima Sekar Maulani; Dewi Halimatus Sa'diah; Rima Wardani; Wendra Putra Pratama; Nugroho Adi Surya (Abdimas: Jurnal Pengabdian Masyarakat Universitas Merdeka Malang, 2024)
The Sumber Tani Farmer Group in Arjasa Village faces limited subsidized fertilizer for tobacco and corn cultivation. Meanwhile, in Arjasa Village there are cassava processing MSMEs, but cassava peel waste is only left to accumulate to rot and even thrown into the river. Therefore, the purpose of this assistance is to overcome the problems of farmer groups through the use of cassava peel waste and a combination of Trichoderma fungi as an alternative to urea fertilizer. This research method includes making fertilizer, mushroom propagation, socialization and training, testing the fertilizer content, and applying it to plants. Laboratory test results show the composition of Savaderma fertilizer is 36.70 percent moisture content; 1.33 percent nitrogen; 0.11 percent phosphorus; and 0.53 percent potassium. Savaderma fertilizer application on tobacco plants showed an increase in plant resistance to pest attacks compared to untreated plants. This research proves the potential of cassava peel waste and Trichoderma fungus as an alternative environmentally friendly fertilizer.